The Common Bean V Gene Encodes Flavonoid 3′5′ Hydroxylase: A Major Mutational Target for Flavonoid Diversity in Angiosperms - McClean, Phillip E.; Lee, Rian; Howe, Kevin; Osborne, Caroline; Grimwood, Jane; Levy, Shawn; Haugrud, Amanda Peters; Plott, Chris; Robinson, Melanie; Skiba, Ryan M.; Tanha, Tabassum; Zamani, Mariam; et al. (Frontiers in Plant Science, 2022)
The classic V (violet, purple) gene of common bean (Phaseolus vulgaris) functions in a complex genetic network that controls seed coat and flower color and flavonoid content. V was cloned to understand its role in the network and the evolution of its orthologs in the Viridiplantae. V mapped genetically to a narrow interval on chromosome Pv06. A candidate gene was selected based on flavonoid analysis and confirmed by recombinational mapping. Protein and domain modelling determined V encodes flavonoid 3’5’ hydroxylase (F3’5’H), a P450 enzyme required for the expression of dihydromyricetin-derived flavonoids in the flavonoid pathway. Eight recessive haplotypes, defined by mutations of key functional domains required for P450 activities, evolved independently in the two bean gene pools from a common ancestral gene. V homologs were identified in Viridiplantae orders by functional domain searches. A phylogenetic analysis determined F3’5’H first appeared in the Streptophyta and is present in only 41% of Angiosperm reference genomes. The evolutionarily-related flavonoid pathway gene flavonoid 3’ hydroxylase (F3’H) is found nearly universally in all Angiosperms. F3’H may be conserved because of its role in abiotic stress, while F3’5’H evolved as a major target gene for the evolution of flower and seed coat color in plants.